Nilai-Nilai Pendidikan dalam Al-Qur’an Surah Ali ‘Imran Ayat 159 dan Al-Qur’an Surah At-Taubah Ayat 128-129: Kajian Perspektif Tafsir Ibnu Katsir - Zidni, A. M. Irfan; Rojudin, Didin (Asatiza: Jurnal Pendidikan, 2023)
This study aims to determine the educational values ​​in the Qur'an surah Ali 'Imran verse 159 and Qur'an surah At-Taubah verses 128-129: A study of the perspective of Ibnu Katsir's interpretation. This research includes library research (library research). Primary data sources and secondary data sources are two categories into which researchers divide data sources. As the main source, used in the Qur'an surah Ali 'Imran verse 159 and in the Qur'an surah At-Taubah verses 128-129perspective of Ibn Kathir's commentary. Meanwhile, secondary data sources include books related to research and scientific journals. Based on the research results obtained that education contained in the Qur'an surah Ali 'Imran verse 159 and Qur'an surah At-Taubah verses 128-129, namely being gentle; sincere in forgiving others; respect the opinions of others; put your trust in Allah; have sympathy and empathy for others; be compassionate to others; always do good and put others first; make God a place to lean on.